Ḍirojio - De, Ramāprasāda (Śaśadhara Prakāśanī : Prāptisthāna Manīshā Granthālaẏa, 1983)
Articles on the life and work of Henry Derozio, 1807-1831, Portuguese born Indian nationalist and teacher of the Hindu College, Calcutta.